Animal Assisted Therapy in a Special Needs Dental Practice: An Interprofessional Model for Anxiety Reduction - Cajares, Caren M.; Rutledge, Carolyn M.; Haney, Tina S. (Journal of Intellectual Disability - Diagnosis and Treatment, 2016)
Purpose: Individuals with intellectual and developmental disabilities (IDD) suffer from poor oral hygiene and periodontal disease that may predispose them to systemic diseases. In order to receive dental care, the assistance of a certified registered nurse anesthetist (CRNA) is often needed. The role of the CRNA is to provide sedation to reduce the high level of anxiety demonstrated by many individuals with intellectual disabilities in the dental suite. However, this can become a challenge with patients that are anxious when they arrive. The purpose of this paper is to describe an interprofessional dental team that added a certified therapy dog and handler to reduce anxiety of individuals with IDD when they arrive in the dental suite. Methods: A convenience sample of 30 individuals with intellectual disability seen for dental care in an outpatient setting met with a therapy dog prior to receiving preventative dental care. Comparisons were made between observed anxiety levels and behaviors measured by the ADAMS (anxiety scale) and a researcher-developed behavior tool prior to and after the interaction with the therapy dog. Results: This program suggested that the addition of the therapy dog to the interprofessional team prior to sedation decreased anxiety levels and improved the behavioral outcomes of the individual with intellectual disabilities. Conclusions: The incorporation of a certified therapy dog and handler as part of an interprofessional healthcare team in the dental suite may pay great dividends in improving the compliance and comfort of the individual with intellectual and developmental disabilities during dental care visits.